The Population Impact of Late Presentation With Advanced HIV Disease and Delayed Antiretroviral Therapy in Adults Receiving HIV Care in Latin America. Issue 6 (29th October 2019) - Belaunzarán-Zamudio, Pablo F; Caro-Vega, Yanink N; Shepherd, Bryan E; Rebeiro, Peter F; Crabtree-Ramírez, Brenda E; Cortes, Claudia P; Grinsztejn, Beatriz; Gotuzzo, Eduardo; Mejia, Fernando; Padgett, Denis; Pape, Jean W; Rouzier, Vanessa; et al.
Abstract: Late presentation to care and antiretroviral therapy (ART) initiation with advanced human immunodeficiency virus (HIV) disease are common in Latin America. We estimated the impact of these conditions on mortality in the region. We included adults enrolled during 2001–2014 at HIV care clinics. We estimated the adjusted attributable risk (AR) and population attributable fraction (PAF) for all-cause mortality of presentation to care with advanced HIV disease (advanced LP), ART initiation with advanced HIV disease, and not initiating ART. Advanced HIV disease was defined as CD4 of <200 cells/μL or acquired immune deficiency syndrome. AR and PAF were derived using marginal structural models. Of 9, 229 patients, 56% presented with advanced HIV disease. ARs of death for advanced LP were 86%, 71%, and 58%, and PAFs were 78%, 58%, and 43% at 1, 5, and 10 years after enrollment. Among people without advanced LP, ARs of death for delaying ART were 39%, 32%, and 37% at 1, 5, and 10 years post-enrollment and PAFs were 20%, 14%, and 15%. Among people with advanced LP, ART decreased the hazard of death by 63% in the first year after enrollment, but 93% of these started ART; thus universal ART among them would reduce mortality by only 10%. Earlier presentation to care and earlier ART initiation would prevent most HIV deaths in Latin America.